A Computational Interrogation of "Big-C" and "Little-c" Creativity. Issue 3 (3rd July 2022) - Sosa, Ricardo; Dijck, Max van
ABSTRACT: The distinction between "Big-C" and "little-c" creativity implies that the generative process of celebrated creators is of a special type or degree. Arguments for and against such a hierarchy of creativity are found in the literature, primarily built on rhetorical argumentation. The aim of this work is to examine the rationale behind Big-C and little-c creativity using explicit and more systematic means of inquiry. We employ computational agent-based simulations to study these constructs, their premises, and their logical implications. The results of this work indicate that hierarchies such as the Big-C and little-c of creativity fail to provide a consistent way to explain and distinguish the generative processes of individual creators. In these computational models of creative social systems, only about half of disruptive changes can be explained by the characteristics of individual agents. This shows how labels like Big-C that are dependent on evaluation outcomes can easily be misattributed by observers to individual creators. This work demonstrates how the use of computational simulations can be useful to examine fundamental ideas about creativity. It shows that the Big-C/little-c distinction is a false dichotomy that should be approached critically by scholars to avoid conflating generative and evaluative dimensions of creativity.